Centralized and Automatic Controls in Ships - Gray, D. (Elsevier Science, 2014)
Centralized and Automatic Controls in Ships provide a non-mathematical basic introduction to the subject of control engineering applied in the marine field. This book is composed of 20 chapters that cover the basic principles of the equipment in ships. The opening chapters deal with ship components, construction, and commissioning routine for certain automated plant. The next chapters consider the basic principles of automatic control and controllers. These topics are followed by discussions on logic units and data processing equipment, other control elements, steam turbines, and diesel engines. Other chapters illustrate the application of control techniques to the major areas of the ship's machinery. The final chapters examine ship and ship's control system commissioning and maintenance. This book is an invaluable source for marine engineers and marine engineering students